If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 3 = 5s + -7 Reorder the terms: 3 + 3a = 5s + -7 Reorder the terms: 3 + 3a = -7 + 5s Solving 3 + 3a = -7 + 5s Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3a = -7 + -3 + 5s Combine like terms: 3 + -3 = 0 0 + 3a = -7 + -3 + 5s 3a = -7 + -3 + 5s Combine like terms: -7 + -3 = -10 3a = -10 + 5s Divide each side by '3'. a = -3.333333333 + 1.666666667s Simplifying a = -3.333333333 + 1.666666667s
| x(x-3)(x-3)=4.8 | | Cos(2x)-3cos(x)-1=0 | | x=3-28 | | 3f-6=2t+2 | | 2i-3=i+14 | | 4x+5=-2x+5 | | 5+6x=x+7 | | (4x+6)+(-5x+2)= | | 2=6x+13x-6 | | 26-n=11 | | z^2+3*z+6=0 | | =13000 | | 4x-7=3(2x+5)-2 | | x^6+7x^5+21x^4+35x^3+35x^2+21x=1064640 | | a=3.14*d | | In(x-1)+(x+2)=1 | | x^3-9x-400=0 | | x+10=61 | | Y+3x=28 | | 3=v-5/3 | | 2sin(2teida)=0 | | (x+7)(2x-7)=0 | | 2x-3=0.5x | | 4(3z-1)-5(z+6)=4(z+1) | | (12-3x)/(2sqrt(6-x)=0 | | (12-3x)/(2√(6-x))=0 | | 18=r+16 | | d=8+4 | | 28+-28+30m= | | 2m-3(5-3m)=3m-15 | | 4(4x+3)-3(2x+6)=2(3x-9)+2x-4 | | -4s=-48 |